The ultrastructure of the intestinal epithelium in Oreochromis niloticus on a diet with different concentrations of zinc - Sartori, T. C F; Dias, E.; Soares, J. C. [UNESP]; Pezzato, Luiz Edivaldo [UNESP] (My University, 2004)
The effects of diets with variable zinc levels on the midgut epithelial cells were studied in Oreochromis niloticus L. One hundred and twenty fry of tilapia were apportioned into 4 experimental groups (I, II, III and IV groups), with 30 fish in each treatment, 5 replicate aquaria per treatment containing 6 fish each. The animals of the 4 groups were fed with isonitrogenous (30% crude protein) and isoenergetic (3000 Kcal/Kg of digestible energy) diets with increasing quantities of zinc (44.59; 149.17; 309.93; 599.67 mg Zn/kg of diet), twice a day, for 93 days. Three fish from each group were sacrificed at 36, 66 and 93 days and samples of midgut were removed for ultrastructural analysis. After 93 days of treatment, 3 animals of each experimental group were used for the analysis of zinc concentration by atomic absorption spectrophotometry. The comparative relative index (CRI) revealed that the animals in groups II, III and IV contained, respectively, 1.99%, 34.67% and 22.78% more zinc than the mean concentration in animals from group I. The ultrastructural analysis showed enterocytes with swelling of smooth surfaced endoplasmic reticulum and dilated mitochondria with variable matrix rarefaction and cristae number reduction in the fish exposed to 599.67 mg Zn/Kg of diet at 66 and 93 days of treatment.
Keywords: Fish; Intestinal epithelium; Tilapia; Ultrastructure; Zinc diet; nitrogen; protein; zinc; animal experiment; atomic absorption spectrometry; caloric intake; cell surface; cell ultrastructure; concentration (parameters); controlled study; dietary intake; digestion; fish; intestine epithelium; intestine epithelium cell; midgut; nonhuman; smooth endoplasmic reticulum; structure analysis; Animal Nutrition Physiology; Animals; Cichlids; Diet; Dose-Response Relationship, Drug; Intestinal Mucosa; Microscopy, Electron, Transmission; Spectrophotometry, Atomic; Zinc; Animalia; Oreochromis; Oreochromis niloticus